Impact of COVID-19 pandemic on psychological health and quality of sleep: An online survey from Kolkata - Mondal, Arijit; Saha, Indranil; Banerjee, Niladri; Saha, Pradeep Kumar; Ghosh, Soumi; Saha, Dwaipayan (Asian Journal of Medical Sciences, 2021)
Background: As a preventive measure to combat COVID-19 pandemic, India has undergone “lockdown” since March 25, 2020. The pandemic and lockdown can impose a psychological impact in the form of fear, anxiety, stress and insomnia etc. Aims and Objective: The aim of the current study is to assess the magnitude of anxiety, depression, stress and poor sleep quality among the adult population of Kolkata, West Bengal amidst COVID-19 pandemic. Materials and Methods: By this online survey using Google forms, a total of 435 responses were received. The online questionnaire comprises of Socio-demographic characteristics, COVID—19 Anxiety Scale (CAS), Perceived Stress Scale 4 (PSS 4), Patient Health Questionnaire-9 (PHQ 9) and Insomnia Severity Index (ISI). Results: COVID-19 related anxiety were almost similar across age groups, sex, marital and educational status. PSS score was found higher in ≤25 years and >40 years age group, those not currently married, students and homemakers. Patient Health Questionnaire scores were found significantly different across all background characteristics categories except for the level of education whereas Insomnia Severity index Scale scores were found significantly more among subjects not currently married and among subjects who were working from home. Conclusions: The current study provides evidence towards the negative psychological impact of the pandemic and reminds us about the need for widespread psychiatric services during and after pandemic.